Designing Automatic Meter Reading System Using Open Source Hardware and Software - Dragan Mlakić; Srete Nikolovski; Emir Alibašić (Institute of Advanced Engineering and Science, 2017)
The importance of quality of the measured values is very dependent on the device that measures these values: the size of the sample, the time of measurement, periods of measurement, the mobility and the robustness of the device, etc. Contemporary devices intended for the measurement of physical quantities that are on the market vary in price, as well as and the quality of the measured values. The rule